Identification of precursors present in fruit juice that lead to the production of guaiacol by Alicyclobacillus Acidoterrestris - Van der Merwe, Enette (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc Food Sc)--University of Stellenbosch, 2011.